Therapeutic Effects of Myeloid Cell Leukemia-1 siRNA on Human Acute Myeloid Leukemia Cells - Hadi Karami; Behzad Baradaran; Ali Esfahani; Masoud Sakhinia; Ebrahim Sakhinia (Tabriz University of Medical Sciences, 2014)
Purpose: Up-regulation of Mcl-1, a known anti-apoptotic protein, is associated with the survival and progression of various malignancies including leukemia. The aim of this study was to explore the effect of Mcl-1 small interference RNA (siRNA) on the proliferation and apoptosis of HL-60 acute myeloid leukemia (AML) cells. Methods: siRNA transfection was performed using Lipofectamine™2000 reagent. Relative mRNA and protein expressions were quantified by quantitative real-time PCR and Western blotting, respectively. Trypan blue assay was performed to assess tumor cell proliferation after siRNA transfection. The cytotoxic effect of Mcl-1 siRNA on leukemic cells was measured using MTT assay. Apoptosis was detected using ELISA cell death assay. Results: Mcl-1 siRNA clearly lowered both Mcl-1 mRNA and protein levels in a time-dependent manner, leading to marked inhibition of cell survival and proliferation. Furthermore, Mcl-1 down-regulation significantly enhanced the extent of HL-60 apoptotic cells. Conclusion: Our results suggest that the down-regulation of Mcl-1 by siRNA can effectively trigger apoptosis and inhibit the proliferation of leukemic cells. Therefore, Mcl-1 siRNA may be a potent adjuvant in AML therapy.